The effect of TiO(2) on the microstructural and electrical properties of low voltage varistor based on (Sn,Ti)O(2) ceramics - Leite, D. R. [UNESP]; Cilense, M. [UNESP]; Orlandi, Marcelo Ornaghi [UNESP]; Bueno, Paulo Roberto [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Wiley-v C H Verlag Gmbh, 2010)
SnO(2)-CoO-Nb(2)O(5) ceramics doped with TiO(2) have been prepared by a conventional oxide method which focuses its application on low voltage varistors. The dopant was added in 0.5 and 1.0% molar concentrations, and samples were investigated by X-ray diffraction, scanning electron microscopy, current vs. voltage, and impedance measurements. The electron microscopy results showed an increase in the mean grain size of ceramics with the addition of TiO(2), which is related to the effect of the dopant on the matrix. The electrical characterization showed that the addition of TiO(2) in 1 mol% provides a system with a good nonlinear coefficient (8.7) and a breakdown electrical field of 6.17 V/cm. These results indicate that this composition can be applied as a low voltage varistor. The impedance data showed that the voltage barrier at the grain boundary is a back-to-back Schottky type and it was demonstrated that the addition of TiO(2) does not significantly modify the barrier. (C) 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim